2019
DOI: 10.3390/ijms20071643
|View full text |Cite
|
Sign up to set email alerts
|

The Secreted Protein MoHrip1 Is Necessary for the Virulence of Magnaporthe oryzae

Abstract: Secreted effectors from Magnaporthe oryzae play critical roles in the interaction with rice to facilitate fungal infection and disease development. M. oryzae-secreted protein MoHrip1 can improve plant defense as an elicitor in vitro, however, its biological function in fungal infection is not clear. In this study, we found that the expression of mohrip1 was significantly induced in the stages of fungal penetration and colonization. Although dispensable for the growth and conidiation, MoHrip1 was necessary for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…According to these features, we then made an in‐depth study of the protein sequence of the 73 WT‐specific proteins and found that 51 proteins annotated with signal peptides and without transmembrane (TM) domains, which 17 of them encoding less than 400 aa, and nine proteins were predicted to be secreted (Table 2). However, only four proteins (hypothetical protein‐encoding gene, MGG_13654; MoHrip1, MGG_15022; MC79, MGG_08041; and MC73, MGG_13275) had been functionally characterized among these proteins in M. oryzae (Table 2) (Guo et al ., 2011; Saitoh et al ., 2012; Nie et al ., 2019). Importantly, MoHrip1 (MGG_15022), first identified from the culture filtrate of M. oryzae , functions as an elicitor to trigger plant defence and was necessary for the full virulence of M. oryzae (Chen et al ., 2012; Nie et al ., 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to these features, we then made an in‐depth study of the protein sequence of the 73 WT‐specific proteins and found that 51 proteins annotated with signal peptides and without transmembrane (TM) domains, which 17 of them encoding less than 400 aa, and nine proteins were predicted to be secreted (Table 2). However, only four proteins (hypothetical protein‐encoding gene, MGG_13654; MoHrip1, MGG_15022; MC79, MGG_08041; and MC73, MGG_13275) had been functionally characterized among these proteins in M. oryzae (Table 2) (Guo et al ., 2011; Saitoh et al ., 2012; Nie et al ., 2019). Importantly, MoHrip1 (MGG_15022), first identified from the culture filtrate of M. oryzae , functions as an elicitor to trigger plant defence and was necessary for the full virulence of M. oryzae (Chen et al ., 2012; Nie et al ., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…However, only four proteins (hypothetical protein‐encoding gene, MGG_13654; MoHrip1, MGG_15022; MC79, MGG_08041; and MC73, MGG_13275) had been functionally characterized among these proteins in M. oryzae (Table 2) (Guo et al ., 2011; Saitoh et al ., 2012; Nie et al ., 2019). Importantly, MoHrip1 (MGG_15022), first identified from the culture filtrate of M. oryzae , functions as an elicitor to trigger plant defence and was necessary for the full virulence of M. oryzae (Chen et al ., 2012; Nie et al ., 2019). These results collectively indicated that MoHrd1 synergizes with MoDer1‐mediated ERAD signalling and is involved in the regulation of pathogenic effector protein secretion in M. oryzae .…”
Section: Resultsmentioning
confidence: 99%
“…It often triggers extra arbitrary effects, such as cell death propagation, when applied to plant microbial interactions with Atg variants [ 90 , 91 ]. A pathogenic bacterium is delivered during the use of these variants, which in turn triggers numerous immune responses [ 92 ]. Selective autophagy is best-characterized with the Cvt pathway.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…From these observations, we posited that beyond secretion, M. oryzae deploys XYL1A as an effector to target and possibly compromise the defense capabilities of the chloroplast during pathogen-host interaction. Furthermore, we examined the expression pattern of pathogenicity-related genes, including Probenazole-inducible protein PBZ1/PR10B (Os12t0555200), pathogenesis-related protein1/PR1A (Os07g0129200), Thaumatin-like pathogenesis-related protein3 precursor/PR5 (Os12g0628600), KAU-RENE_SYNTHASE-LIKE_7/KSL7 (Os02g0570400), K A U R E N E _ S Y N T H A S E -L I K E _ 1 0 / K S L 1 0 (Os12g0491800), syn-pimaradiene 3-monooxygenase/ KOL4 (Os06g0569500), CytochromeP450/CYP76M8 (Os02g0569400), NARINGENIN_7-O-METHYL-TRANSFERASE/NOMT (Os12g0240900), Phenylalanine ammonia-lyase/ (Os05g0427400), and chitinase1/ Cht1 (Os06g0726200) (Jeon et al 2020;Nie et al 2019) in 14-21-days old CO39 rice seedlings independently challenged with the individual strains at 12-hpi. These examinations revealed a significant upregulation in the expression level of putative chloroplast localized PR genes (Additional file 1: Table S2), particularly, OsNOMT and OsKSL10 in rice seedlings inoculated with ΔMoxyl1A (Fig.…”
Section: Oryzae Likely Deploys Moxyl1a As Putative Cytoplasmic Effect...mentioning
confidence: 99%